The Effect of Science on the Second World War - Hartcup, G. author. aut Link
XVI, 214 p.
Keywords: The latest advances in science were fully exploited in the Second World War. They included radar, sonar, improved radio, methods of reducing disease, primitive computers, the new science of operational research and, finally, the atomic bomb, necessarily developed like all wartime technology in a remarkably short time. Such progress would have been impossible without the cooperation of Allied scientists with the military. The Axis powers' failure to recognise this was a major factor in their defeat.